ANALISIS KESESUAIAN PENERAPAN STANDAR PELAYANAN KEFARMASIAN DI PUSKESMAS KABUPATEN MINAHASA UTARA - Stacy Harry Tamawiwy; Widya Astuty Lolo; Imam Jayanto (PHARMACON, 2022)
ABSTRACT Pharmaceutical service standards have been regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016 concerning Pharmaceutical Service Standards at Public Health Center, but there are pharmaceutical service activities that have not been implemented, including destruction and withdrawal of drugs, monitoring of drug side effects, and drug therapy monitoring. This study aims to determine the percentage of compliance with the application of pharmaceutical standards at the Health Center of North Minahasa Regency based on the Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016. This research is a descriptive type of research with a prospective and retrospective approach. The population in this study were all Public Health Centers in North Minahasa Regency and the sample in this study were Public Health Center located on Jalan Manado - Bitung as many as 4. Retrieval of data are through interviews, questionnaires, and observations. Based on the results of the study, the percentage of compliance with the application of pharmaceutical service standards with the Minister of Health Number 74 of 2016 is 72,14%. It can be concluded that the suitability of the application of pharmaceutical service standards at the Health Center of North Minahasa Regency is included in the sufficient category. Keyword: Public Health Center, Pharmaceutical Service Standards. ABSTRAK Standar pelayanan kefarmasian telah diatur dalam Peraturan Menteri Kesehatan Republik Indonesia Nomor 74 Tahun 2016 Tentang Standar Pelayanan Kefarnasian di Puskesmas, akan tetapi terdapat kegiatan pelayanan kefarmasian yang belum terlaksana, antara lain pemusnahan dan penarikan obat, monitoring efek samping obat, serta pemantauan terapi obat. Penelitian ini bertujuan untuk mengetahui persentase kesesuaian penerapan standar kefarmasian di Puskesmas Kabupaten Minahasa Utara berdasarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 74 Tahun 2016. Penelitian ini merupakan jenis penelitian deskriptif dengan pendekatan prospektif dan retrospektif. Populasi dalam penelitian ini yaitu seluruh Puskesmas di Kabupaten Minahasa Utara dan sampel dalam penelitian ini yaitu Puskesmas yang berada di Jalan Manado – Bitung sebanyak 4 Puskesmas. Pengambilan data melalui wawancara, kuesioner, dan observasi. Berdasarkan hasil penelitian, diperoleh persentase kesesuaian penerapan standar pelayanan kefarmasian dengan Permenkes Nomor 74 Tahun 2016 sebesar 72,14%. Dapat disimpulkan bahwa kesesuaiaan penerapan standar pelayanan kefarmasian di Puskesmas Kabupaten Minahasa Utara termasuk dalam kategori cukup. Kata Kunci: Puskesmas, Standar Pelayanan Kefarmasian